Evaluation of ethanolysis with immobilized Candida antarctica lipase for regiospecific analysis of triacylglycerols containing highly unsaturated fatty acids - Shen, Zhiping; Wijesundera, Chakra (Journal of the American Oil Chemists' Society, 2006)
Abstract The suitability of a recently proposed method based on ethanolysis with immobilized Candida antarctica lipase for regiospecific analysis of oils containing long‐chain PUFA such as [PA and DHA has been evaluated using selected marine oils and regio‐isomerically enriched synthetic TAG substrates. 1,3‐Regios‐electivity of the lipase was enhanced when the ethanolysis was conducted in a high excess of ethanol, typically 10–50 times by weight of the oil. This enabled the reaction to be conducted on a milligram scale. However, irrespective of the ethanol‐to‐oil ratio, C. antarctica lipase released FA from TAG at different rates depending on the degree of unsaturation and/or chain length of the FA. Differences in lipolysis rates were particularly significant for EPA and DHA, with EPA released faster than DHA. Although DHA can be measured with reasonable accuracy by ethanolysis with C. antarctica , the method requires further optimization before it can be adopted for reliable regiospecific analyses that are as accurate as those obtainable by 13 C NMR analysis for all major FA occurring in oils rich in long‐chain PUFA.